Penyuluhan Tentang Efektivitas Pemberian ASI Eksklusif Pada Bayi Dalam Mengatasi Stunting - Adinda Lestari; Selvia Mona Junita; Wirna Mailisa; Cek Sindis Musapira; Meriwati Meriwati; Jun Musnadi Is; Sufyan Anwar (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Stunting remains a significant public health issue in Indonesia. One of the government’s efforts to address this problem is through the exclusive breastfeeding program. However, the achievement of this program is still below expectations. This community service activity was conducted at the Langkak Village Hall, Kuala Pesisir District, Nagan Raya Regency, using lectures and discussions as methods. The participants consisted of 27 individuals, including pregnant women and mothers with toddlers. The activity took place on Thursday, August 8, 2024, for a duration of 90 minutes, and was attended by 17 participants. During the discussion/Q&A session, seven participants actively asked questions related to exclusive breastfeeding and shared the challenges they encountered in practicing it. The results indicated the need for a more structured strategy to enhance understanding and implementation of exclusive breastfeeding within the community. One proposed strategy is the establishment of the “Family Loves Baby” class, based on a SWOT analysis approach. This class would involve one family member from each household with an infant aged 0–6 months, serving as a support system for exclusive breastfeeding. Additionally, Posyandu cadres are expected to play an active role in providing education and raising awareness among mothers, families, and the broader community about the importance of exclusive breastfeeding to prevent stunting. This approach is expected to serve as a concrete step in supporting the government’s program to reduce stunting rates in the region.